Emphysematous pyelonephritis after urinary diversion by percutaneous nephrostomy in patient with advanced cervical cancer: A case report - Jeferson Rodrigo Zanon; Henrique Durante; Leandro de Medeiros Nóbrega; Guilherme Accorsi; Priscila Grecca Pedrão; Ricardo dos Reis (SAGE Open Medical Case Reports, 2023)
Emphysematous pyelonephritis is a severe kidney infection that is common in women and patients with diabetes mellitus, but rare in cancer patients. A 64-year-old patient with advanced uterine cervical cancer developed emphysematous pyelonephritis after urine diversion by percutaneous nephrostomy of the left kidney, which is a possible approach to this infection. Antibiotic therapy was started to achieve clinical improvement and preserve renal function, and radical nephrectomy was not an option due to the functional exclusion of the contralateral kidney. The patient progressed with worsening renal function; thus, she started outpatient hemodialysis, with improvement of the uremic encephalopathy. She died 7.7 months after admission, 1 month after treatment for emphysematous pyelonephritis. Treatment should be adjusted to the patients’ needs, including maintenance of hemodialysis to improve symptoms. Further investigation is needed to identify possible causes and prevent emphysematous pyelonephritis in cancer patients.